2020
DOI: 10.3390/ijms21155336
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypoxic and Hyperoxic Preconditioning on Endothelial Function in a Model of Myocardial Ischemia-Reperfusion Injury with Cardiopulmonary Bypass (Experimental Study)

Abstract: The aim of the experiment was to evaluate the effect of preconditioning based on changes in inspiratory oxygen fraction on endothelial function in the model of ischemia-reperfusion injury of the myocardium in the condition of cardiopulmonary bypass. The prospective randomized study included 32 rabbits divided into four groups: hypoxic preconditioning, hyperoxic preconditioning, hypoxic-hyperoxic preconditioning, and control group. All animals were anesthetized and mechanically ventilated. We provided precondit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
2
2
Order By: Relevance
“…A few changes were in conjunction with preconditioning: less reduction of nitrate concentration at the end of the surgery, and stabilization of NO metabolites at 24 h after surgery as compared to the control group. Contrary to our recent experimental study, where we have found that HHP had an infarctlimiting effect, balanced NO metabolites, and reduced ET-1 hyperproduction in the simulation of IRI under the conditions of CPB [47]. Besides, we observed statistically significant differences in ET-1 production and NO metabolites imbalance in patients with postoperative complications compared with noncomplicated patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A few changes were in conjunction with preconditioning: less reduction of nitrate concentration at the end of the surgery, and stabilization of NO metabolites at 24 h after surgery as compared to the control group. Contrary to our recent experimental study, where we have found that HHP had an infarctlimiting effect, balanced NO metabolites, and reduced ET-1 hyperproduction in the simulation of IRI under the conditions of CPB [47]. Besides, we observed statistically significant differences in ET-1 production and NO metabolites imbalance in patients with postoperative complications compared with noncomplicated patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Sample size calculation was carried out for the study with 130 patients randomized in the proportion of 1:1. Due to the lack of a unified protocol, we developed our protocol of preconditioning, which allows us to simulate the phenomenon of hypoxic-hyperoxic preconditioning in animals and humans [46,47]. The sample size calculation was based on our previous results [46].…”
Section: Discussionmentioning
confidence: 99%
“…A few changes were in conjunction with preconditioning: Less reduction in nitrate concentration at the end of the surgery and stabilization of NO metabolites at 24 h after surgery as compared to the control group. This is contrary to our recent experimental study where we have found that HHP had an infarct-limiting effect, balanced NO metabolites, and reduced ET-1 hyperproduction in the simulation of IRI under the conditions of CPB [ 25 ]. Additionally, we observed statistically significant differences in ET-1 production and a NO metabolites imbalance in patients with postoperative complications compared with noncomplicated patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Sample size calculation was provided for the study with 130 patients randomized into the two equal groups. Due to the lack of a unified protocol, we developed our protocol of preconditioning, which allows us to simulate the phenomenon of hypoxic–hyperoxic preconditioning in animals and humans [ 24 , 25 ]. The sample size calculation was based on our previous results [ 24 ].…”
Section: Methodsmentioning
confidence: 99%